BDNF serum levels and promoter methylation of BDNF exon I, IV and VI in depressed patients receiving electroconvulsive therapy - Kleimann, Alexandra; Kotsiari, Alexandra; Sperling, Wolfgang; Groeschl, Michael; Heberlein, Annemarie; Kahl, Kai G.; Hillemacher, Thomas; Bleich, Stefan; Kornhuber, Johannes; Frieling, Helge (Journal of Neural Transmission, 2015)
We examined potential changes in brain-derived neurotrophic factor (BDNF) serum levels and promoter methylation of the BDNF gene in 11 patients with treatment-resistant major depressive disorder during a series of electroconvulsive therapy (ECT). Blood samples were taken before, 1 and 24 h after ECT treatment sessions 1, 4, 7 and 10. Patients remitting under ECT had significantly lower mean promoter methylation rates, especially concerning the exon I promoter, compared to non-remitters (both p < 0.002). These findings may point to a depression subtype in which ECT is particularly beneficial.
EVALuna2:23744